Potential of Stingless Beekeeping in Community Empowerment Strategy for Building Sustainable Creative Economy in a Forest Farmer Group of Puncak Labuang, Padang City - Herwina, Henny; Jasmi , Jasmi; Dahelmi, Dahelmi; Ratni, Eli; Janra, Muhammad Nazri; Ilmi, Miftahul; Azura, Nabilah Rahmachila; Rezvi, Syakira Tiara (Warta Pengabdian Andalas, 2025)
The Forest Farmer Group of Puncak Labuang (FFGPL) manages a 194-hectare community forest in Limau Manis, Padang, contributing to the livelihood of community through agriculture and ecotourism. The forest productivity comes as high-value commodities such as durian, mangosteen, and coffee, as well as ecotourism activities like camping and hiking; all of which boost local economy while sustaining the surrounding environmental. Having diverse vegetation, the forest presents an opportunity for farming the stingless bee (galo-galo) as a promising innovative economic initiative. This program aligns with the program of West Sumatra Provincial Government to achieve position as production centre for honey. Some challenges such as low production of bee colonies appear from the lack of knowledge in farming techniques and insufficiency of food sources for colonies which hinder the progress. From June to December 2024, a community service program had been implemented to address these challenges. Activities included socialization, demonstrations, and training in bee farming techniques, supported by a team of experts. The education focused on the potential of galo-galo farming and strategies for marketing local products. Additionally, training sessions for Micro, Small, and Medium Enterprises (MSMEs), along with honey product exhibitions, had successfully raised public awareness and improved the competitiveness of local products. As a result of this program, there was a notable improvement in community skills and knowledge, contributing to the sustainability of local economy and preservation of biodiversity. FFGPL has the potential to become a model for community empowerment based on natural resources, leading to significant improvements in community welfare.